Konteksty występowania leksemów Polak, Polska i polski w zbiorze modlitw powszechnych Módlmy się wspólnie o. Ireneusza Żołnierczyka - Pałucka-Czerniak, Iwona (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The article presents the results of a pragmalinguistic analysis of the linguistic contexts of the lexemes Polska, Polak and polski (Poland, Pole, Polish) in the collection of common prayers written by Father Ireneusz Żołnierczyk in 1984. The analysis allows the author to present the way of speaking and modelling the thinking on homeland within a specific given community, place and time. The material under scrutiny consists of the collection of common prayers that is to provide a clear illustration for the mechanisms to create and sustain the sense of religious and national unity. The collection, in the form of an auxiliary book for liturgy, had in the past a particular impact as a pattern providing a template in creating specific communiques during the litugy of the high mass in the Catholic Church. The supplications in the prayers execute a well-established and fixed general pattern, shaping the model of a believer as a hard-working, industrious and the virtuous Pole-Catholic. Within the lexical layer of the prayers there is no particularisation or direct references to political, economic and social situation in Poland, though the participants in the common prayer are in position to contextually read a given passage or hear a modified supplication (appropriately adjusted to specific or current events).